PEMBUATAN APLIKASI POINT OF SALES BERBASIS IPHONE OPERATING SYSTEM UNTUK UD. SINAR MAS: DEVELOPMENT OF IOS-BASED POS APPLICATIONS FOR UD. SINAR MAS - Wijangga, Hanjaya; Soekamto, Yosua Setyawan (Universitas Lancang Kuning, 2023)
UD. Sinar Mas is a distribution company selling chemicals. UD. Sinar Mas records transactions using methods that are still manual or traditional. Where is the transaction method at UD. Sinar Mas also has several kinds of transaction systems such as receivables, debts, and there is also a barter sales of jerry cans, customers bring their own drums, or leave the drums with UD. Sinar Mas. The recording method in UD transactions. Sinar Mas, namely recording supplier names, recording customer names, sales transaction dates, purchase transaction dates, maturity dates. Because many transaction systems are recorded, it causes user errors such as missing notes, viewing the due date as well as errors in recording the due date when to collect debts, then how much customer debt remains, whether the goods have been sent by the customer or not, wrong mention of the price to a particular customer , an incorrect calculation of the amount sent is sometimes too less or too much, where the most fatal is the incorrect mention of the price to the customer because there are several customers whose prices are differentiated because of certain cases such as customers who have subscribed for a long time and also the remaining stock counting system which is still manual using approximate method so that it cannot produce a definite stock. The method that will be used for solving the problem is by creating an IOS-based application to help record transactions in UD. Sinar Mas. The result of this application is in the form of a cashier application that can record expenses, income and others. The purpose of this research is to help UD companies. Sinar Mas to record transactions more easily. From this problem, the author's solution is to design and design an iOS-based POS application. The POS application is made on the iOS platform because the owner of UD. Sinar Mas uses iOS as the main device. To save the data will be stored in SQL. The test is carried out using the UMUX method. The results of the test can be concluded that the resulting score is quite good. However, in the application test, there were a few obstacles, such as users experiencing confusion when pressing buttons and so on. Apart from that it runs pretty smoothly. The features that have been implemented have met the needs of the user.